Catastrophic antiphospholipid syndrome: a narrative review - Maria Giulia Tinti; Vincenzo Carnevale; Angela De Matthaeis; Antonio Varriale; Angelo De Cata (Verduci Editore, 2019)
The catastrophic antiphospholipid syndrome (CAPS) is a lifethreatening disorder characterized by the rapid development of multiple organs/systems thrombosis, in patients with persistently detectable antiphospholipid antibodies. The vascular occlusions predominantly affect small vessels, leading to a disseminated thrombotic microangiopathic syndrome. Most CAPS episodes are related to the presence of a precipitating factor, such as infections and malignant diseases, usually ending up in multiple organ failure. Clinical manifestations may vary according to the extent of the thrombosis, predominantly affecting kidneys, lungs, brain, heart, and skin. Treatment is based on the administration of anticoagulants, corticosteroids, plasma exchange and/or intravenous immunoglobulins. Cyclophosphamide is recommended in CAPS associated with systemic lupus erythematosus. Additionally, rituximab and eculizumab have been used in refractory cases. Overall mortality is still 36.9%, despite recent progress in the therapeutic approach.